Geoscientific data indicate Storegga slide tsunami impact on the southeastern German North Sea coast - Andreas Vött; Manfred Frechen; Frank Sirocko (PANGAEA, 2024)
The Storegga slide tsunami (SST) at ca. 8100 ± 100-250 cal BP is known to be the largest tsunami that affected the North Sea during the entire Holocene. Geological traces of tsunami landfall were discovered along the coasts of Norway, Scotland, England, Denmark, the Faroes and Shetland Islands. So far, the German North Sea coast has been considered as being well protected due to the wide continental shelf and predominant shallow water depths, both assumed to dissipate tsunami wave energy significantly, thus hindering SST propagation dynamics. Our research was carried out in order to clarify if the SST reached the German Bight and if corresponding sediment markers can be found. Our study is based on a 20 m long sediment core (GAR 1A) recovered from Eiderstedt Peninsula near Garding in North Frisia. In this data repository, we present high-resolution Direct Push sensing data as well as grain size and magnetic susceptibility data, which were used to reconstruct palaeoenvironmental and palaeogeographical conditions.